Synergistic reduction of graphene oxide using vitamin C and urea: Enhanced efficiency and material properties - Fei-hu Zeng; SyYi Sim; Zhi-wen Wang; Feng Wang (PLoS ONE, 2025)
Synergistic reduction of graphene oxide (GO) using different reducing agents represents an effective approach for reduced graphene oxide (rGO) synthesis. In this study, the rGO (rGO-Vc+Urea) was prepared by combining vitamin C (Vc) and urea as co-reducing agents with the modified Hummer’s method. Compared to samples reduced solely with Vc or urea, the co-reducing agents significantly reduced the required reaction time (to 2 hours) and temperature (to 120°C), while yielding material with superior electrical resistivity (1.2 Ω·cm). The structure of the samples was characterized using XRD, FT-IR, Raman spectroscopy, BET surface area analysis, and SEM. Results indicate that the sample prepared from co-reducing agents possesses a typical graphene structure and incorporates C-N bonds. Furthermore, rGO-Vc+Urea exhibits a higher degree of structural order, as evidenced by a lower Raman (Iᴅ/IG = 0.75), compared to rGO-Vc (Iᴅ/IG = 0.91) and rGO-Urea (Iᴅ/IG = 1.49), along with a higher specific surface area (88.60 m2/g). The reduction mechanism of the co-reducing agents was investigated. It was revealed that the alkaline environment generated by urea enhances Vc’s ability to reduce oxygen-containing functional groups in GO, specifically hydroxyl, epoxy, carbonyl, and carboxyl groups, and promotes the elimination of CO2 released during the reaction. This strategy of employing synergistic multiple reducing agents offers new perspectives for the preparation of rGO.